Pengaruh Brand Image, Kualitas Produk Dan Word Of Mouth Terhadap Keputusan Pembelian Produk Merk Eiger (Studi Pada Mahasiswa Kampus FEB Unisma Angkatan 2018) - Fani Ary Sandy; Muhammad Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study was to determine how the influence of brand image, product quality and word of mouth on purchasing decisions. The population in this study were students of the FEB campus at the Islamic University of Malang Batch 2018. The Non-Probability Sampling method was Purposive Sampling with a sample of 90 respondents. The results of the study partially show that: 1) There is a positive and significant influence of brand image on purchasing decisions for Eiger brand products 2) There is a positive and significant effect of product quality on purchasing decisions for Eiger brand products 3) There is is a positive and significant influence of word of mouth on purchasing decisions Eiger brand products. All independent variables have a simultaneous effect on purchasing decisions for Eiger brand products. Keywords: Brand Image, Product Quality, Word Of Mouth And Purchase Decision.